Relationship between Work Resources and Teachers’ Job Well-being - Sidek, Zalifah; Surat , Shahlan; Kutty, Faridah Mydin (International Journal of Psychosocial Rehabilitation, 2020)
Work resources contribute job’s motivation as they help in teachers’ self-development and well-being. This support of work resources leads to teachers’ retention and increase in motivation throughout the day. The resources found at work can contribute to the teachers’ well-being psychologically and their job satisfaction in schools. On the other hand, a lack of resources can cause teachers’ emotional, spiritual and physical problems because they are unable to meet the demands of their day-to-day work. This study was conducted to identify the relationship between work resources and teachers’ well-being. Respondents consisting of 460 teachers were selected through a proportionate stratified random sampling technique. Instruments using the 5-point and 7-point Likert scales were analyzed using Structural Equation Model Analysis (SEM) to identify the relationship of work resources variables with teacher job well-being. The findings show that work resources have a significant relationship with teachers’ well-being. Support from administrators, colleagues and good relationships between teachers and pupils are valuable and contribute significantly to teachers’ psychological health. In fact, it has contributed to the retention of high-quality work and teachers’ well-being.